A Hands-On Guide to Designing Embedded Systems - Taylor, Adam (Artech House, 2021)
This practical resource introduces readers to the design of field programmable gate array systems (FPGAs). Techniques and principles that can be applied by the engineer to understand challenges before starting a project are presented. The book provides a framework from which to work and approach development of embedded systems that will give readers a better understanding of the issues at hand and can develop solution which presents lower technical and programmatic risk and a faster time to market.Programmatic and system considerations are introduced, providing an overview of the engineering life cycle when developing an electronic solution from concept to completion. Hardware design architecture is discussed to help develop an architecture to meet the requirements placed upon it, and the trade-offs required to achieve the budget. The FPGA development lifecycle and the inputs and outputs from each stage, including design, test benches, synthesis, mapping, place and route and power estimation, are also presented. Finally, the importance of reliability, why it needs to be considered, the current standards that exist, and the impact of not considering this is explained. Written by experts in the field, this is the first book by "engineers in the trenches" that presents FPGA design on a practical level.